Utilization of FAD Distribution in South Buton Waters as a Fishing App by Purse Sein Fishermen in Kadatua District, Selatan Buton Regency - Hamar, Bahtiar; Bone, Abdul Hadi (Journal of Asian Multicultural Research for Economy and Management Study, 2021)
Fish Aggregating Devices (FAD's) have long been used by fishermen in South Buton Regency. This study aims to determine the utilization of FAD distribution as a fishing aid by purse sein vessels in the waters of Kadatua District, South Buton Regency. This study aims to determine the utilization of FAD distribution as a fishing tool by purse sein vessels in Kadatua District, South Buton Regency. Data collection methods include FAD point data taken from GPS (Global Position System) fishermen and dominant catch data from purse sein fishermen. The results of the study obtained data on the distribution of FADs in Kadatua District spread between a distance of 0-12 miles, during the study the coordinates of FADs were obtained as many as 79 coordinate points owned by fishermen in Kadatua District. FADs used by purse sein fishermen to carry out fishing operations have 24 FAD points, which are spread over a distance of 0 – 12 miles. In April the distribution of FADs used as fishing aids by purse sein vessels was at a distance of ± 0 – 12 miles, while in May and June FADs used as fishing aids were at a distance of ± 2 – 12 miles. The dominant fish catch data for purse sein fishermen is 690 kg in April, 525 kg in May and 735 kg in June. The dominant catch during the study was dominated by scad fish (Decapterus spp). The level of effectiveness of the dominant catch of purse sein fishermen is highest at a distance of 4-12 miles with a total catch of 1,070 kg of the total catch of 1,950 kg.